Geographic Information System Produksi Energi dan Pertambangan Kabupaten Musi Banyuasin - Usman Ependi (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
Energy and mining reporting have to conduct for the exploration company in order to make control while exploration. Government control can perform by making profiling of energy and mining data that exist in the area as consideration in taking policy or decision. Stages of energy and mining reporting are very important to do especially in areas that have energy and mining resources such as Musi Banyuasin regency. Profiling can performed by mapping the location of energy and mining results using a geographic information system (GIS) to organize data between explorers and governments. Based on these conditions GIS was developed using a technique that prioritizes user needs with extreme programming development techniques. The result of GIS development shows that the processing of data becomes information based on spatial and non-spatial data with the final result of energy and mining report. The report presented can be used as a report to the relevant parties as an effort to open data of energy and mining as material in decision-making or policy. Geographic information system generated systematically developed using extreme programming approach with five stages of exploration, planning, iteration, production and maintenance so that it can run funtionaly according to its function